Efeito da termorretificação nas propriedades tecnológicas do bambu - Brito, Flávia Maria Silva (2013)
This work aimed to evaluate the physical and anatomical characteristics of bamboo "in natura", analysing the effects of thermal treatment on the technological properties of glued laminated bamboo thermo-modified (GLBT) and in your natural durability. A total of four culms were collected in age adulthood and cut every to 2.0 m and divided into four lengthwise sections that were immersed in water for 10 days and air-dried. The sections were transformed into flights with dimensions of 0.5 x 3,5 x 45 cm (thickness x width x length) and thermal treated to 100, 140, 160, 180 and 200 °C for one hour for each temperature. T he adhesives used were “Cascophen RS-216-M”, based resorcinol – formaldehyde, “Cascamite PL-2030”,based on urea - formaldehyde, both thermoset and thermoplastic based on one polyvinylacetate, “Cascorez 2500”. The flights thermal treated were scaled according to each proposed test. It was observed that the bamboo culms have a frequency of 0 to 4 vessels.mm-2, whith mean of vessels.mm-2, with long and narrow fibres with length average of 2.72 mm. The basic specific gravity was of 0.66 g.cm-3 and volumetric shrinkage of 15.41%. The total extractives and lignin contents increased as the temperature increase, and holocellulose content has been reduced. Since the temperature of 160 °C was a gain in durability natural bamboo and the dimensional stability of GLBT adhered to RF, but there was a decrease in the values of specific gravity and mechanical properties of the material.